Diksyunaryong monolingwal sa Filipino. - McFarland Curtis D. (De La Salle University Press, 2005)
A project of Komisyon ng Wikang Filipino, this dictionary uses Filipino to explain the meaning of words. It contains about 30,000 entries and includes terms derived from different fields such as: literature, bilingual education, sculpture, painting, mechanics, ceramics, welding, refrigeration and air conditioning, printing, metal works, electricity, electronics, car mechanics and technical writing. The orthography of the entries is based on the guidelines set by the Linangan ng Wika sa Pilipinas in 1987.